Cultural Meaning and Belief in Pamatè Tradition on Society of Aeng Tong-tong, Sumenep, Madura: Ethnolinguistic Study - Hodairiyah Hodairiyah; Izzuddin A. Hakim; Ahmad Yasid (MOZAIK HUMANIORA, 2021)
This study aims to explore the cultural meaning and belief of Pamatè tradition at Aeng Tong-tong society in Sumenep. Pamatè tradition is known to be rich of verbal and nonverbal expressions, such as word, phrase, clause, and sentence. To pursue the aim of this study, qualitative descriptive method together with ethnolinguistic approach, especially ethnoscience analysis model was used to analyse the meaning beyond verbal and nonverbal expressions of Pamatè tradition at Madurese society. To collect data, purposive sampling was used to get complete data correlated with Pamatè tradition. Besides, snowball sampling was used to determine key informants who know tradition well through interview and documentation techniques. The results of this study revealed that there are verbal and nonverbal expressions. Verbal expressions found are utterances involving term, phrase, clause, sentence, such as (a) Mandi’in, panyompet, panotop, panyundhâng, senga’ on laon mun nyaba’, sabhârâng, aniat kula awudhuaginah mayyit karana Allah ta’aala; (b) Pundhu’, labun taleppet’; (c) esambhajangagi; and (d) ependem. Meanwhile, non-verbal expressions found are instruments and things correlated with pamatè tradition, such as aeng socceh, sere, sabun, kapas, kan geddhâng, soroi, sampo, dinding are, labun, konyi’, lu belluh. In short, pamaté tradition is a form of local wisdom of the people of Aeng Tong-tong, containing symbols and oral traditions reflected in the verbal and non-verbal expressions.